Do Gaming Simulations Substantiate That We Know More Than We Can Tell?. (August 2021) - van Haaften, M. A.; Lefter, I.; Lukosch, H.; van Kooten, O.; Brazier, F.
Background: Revealingtacit knowledge often is seen as very valuable for organizations, although it is usually challenging to enunciate and share this type of knowledge. Methods: This study uses aparticipatory design and the application of a board gaming simulation as instruments to extract tacit knowledge. To illustrate this application, the gaming simulation is played with entrepreneurs from horticulture.Horticulture represents a complex social system where tacit knowledge plays a major role in the trade process. A participatory design process is used to explore whether the design and play of gaming simulations enable participants to explicate their tacit knowledge. Participants' participation in designing the gaming simulation explicated that reconstructing reality was a prerequisite for their commitment. Results: The results from playingsimulation sessions show that participants were able to: (1) narrow down the anecdotic behaviour to a few factors; (2) to structure these factors; (3) explore how these factors relate to trade barriers and (4) to explain which tactics are applied to foster trade. Conclusion: The educational value of this study is that it helped entrepreneurs in understanding complex real-life situations.